New challenges for law enforcement agencies of Ukraine in the context of the ongoing Russian aggression - Kobko, Yevhen; Korniienko, Maksym; Koniushenko, Yana; Starosta, Vitalii; Prysyazhnyuk, Olexandr (DIXI, 2025)
The importance of this scientific research is due to the multi-vector nature of the challenges faced by law enforcement agencies of Ukraine in the context of the ongoing aggression by Russia. In the context of the study, attention is focused on problematic aspects in the field of logistical support of law enforcement agencies. Firstly, it concerns such problematic issues as lack of adequate lighting; security difficulties in organizing work, especially in those cities that are subject to constant shelling; inability to effectively ensure public safety and order, etc. Analyzing the security challenges, it was noted that the scientific community has not developed a comprehensive approach to the tactics of law enforcement agencies in the face of radiation contamination, an emergency with nitrogen emissions, artificial flooding caused by the destruction of a hydroelectric power plant, etc. The tactics of law enforcement agencies during the inspection of the site of a missile strike in the face of possible repeated attacks, and the interaction of various bodies and units to ensure their maximum safety also need to be developed. An important area of scientific research is to rethink the use of special means and weapons by law enforcement agencies, as the use of the latest tactical techniques best allows them to fulfill the tasks facing law enforcement agencies in the context of armed aggression and countermeasures. Law enforcement agencies also face challenges related to information flows of narratives.